Classic writings for a phenomenology of practice - Van Manen, Michael; Van Manen, Max (New York : Routledge, 2021)
Classic Writings for a Phenomenology of Practice features examples of newly translated classic phenomenological texts that have been largely forgotten or misunderstood. The writings are unique in that they speak to the practice of doing phenomenological research for the purpose of gaining insights and better understandings regarding aspects of professional practice and ordinary life phenomena and events. Phenomenology does not have to be impenetrable philosophy, dealing with tedious technical issues. Instead, phenomenology may offer relevance, value, and enduring allure to readers and researchers who are engaged with the quotidian life experiences and events of students, patients, clients, friends, and other individuals. This phenomenological approach aims to stay as close as possible to the ordinary events of everyday life: seeing the first smile ofa child, feeling compulsive, being humorous, having a conversation, experiencing childhood secrecy, encountering newthings--topics that span a manifold of life experiences. In this collection of classic phenomenological writings, each author is thoughtfully introduced, and each text is followed by a conversational descant: a reflection on the phenomenological reflection. The presentation of these classic writings and their reflections aims to show us what it means to do phenomenology directly on the phenomena that we live--thus asking us to be attentive to the fascinating varieties and subtleties of primal lived experiences and consciousness in all its remarkable complexities. This book is relevant for scholars and students who are interested in human science research and the origins and practices of the phenomenological method.
11 The "Secret Place" in the Life of the Child: [De "Geheime Plaats" in het Leven van het Kind, 1953/1967] -- 12 Descant on "The 'Secret Place' in the Life of the Child" -- 13 The Thing in the World of the Child: [Das Ding in der Welt des Kindes, 1956] -- 14 Descant on "The Thing in the World of the Child" -- 15 Johannes Linschoten -- 16 On Humour: [Over de Humor, 1951] -- 17 Descant on "On Humour" -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Phenomenology; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research